Faktor Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja UPTD Puskesmas Siak Hulu I Dan III Tahun 2018 - Elvanita Nita; Buchari Lapau; Oktavia Dewi (Sistem Informasi, 2019)
Anemia in pregnancy is a condition where hemoglobin (Hb) levels in pregnant women in trimester I and III <11 grams%, while in trimester II Hb levels <10.5%. Normal hemoglobin levels in pregnant women> 11 grams%. UPTD Siak Hulu Health Centers I and III were the health centers that had the highest anemia cases in kampar regency in two consecutive years, namely 14.60% and 67.68% in 2016, while in 2017 were 63.63% and 85.83%. This study aims to determine the factors associated with the incidence of anemia in pregnant women in the work area of ​​the UPTD Puskesmas Siak Hulu I and III in 2018. The research method uses design cross sectional. The population is pregnant women in the third trimester of 2018. The number of samples is 211. Sampling is done by simple random sampling. Data analysis was carried out by univariate, bivariate and multivariate with multiple logistic regression. The results showed that the variables related to cause and effect on the incidence of anemia in pregnant women in the work area of ​​the Siak Hulu I and III UPTD Puskesmas were adherence to Fe tablet consumption OR = 2,74 (95% CI=1.043-7.210). Recommended to health workers to conduct KIE activities and promotions for prospective pregnant women, pregnant women and communities in the region.